Modulation of The Laser-Induced Phase Transition of VO2/W-TiO2 n-n Heterojunction
To solve the contradiction between the low phase transition threshold and the infrared switching efficiency (r) of VO₂, a VO₂/W-TiO₂ n-n heterojunction was fabricated on the K9 glass substrate with the magnetron sputtering. The effects of W doping for TiO₂ layer on the heterojunction phase transition performance were investigated. An appropriate W doping increases the carrier concentration (n) and its mobility (μ), thereby reducing both the thermotropic phase transition threshold (Tc) and the laser-induced phase transition threshold (Pc) of the heterojunction. The heterojunction doped 1.37 at% W exhibits the optimal comprehensive performance. The r of the heterojunction is up to 56.8%, the Tc decreases to 54.3 °C, and the Pc to 51.8 W/cm². , number=2, journal=Journal of Electronics and Electrical Engineering, author=Shi, Weizheng and Zhao, Leran and Xu, Qiujing and Zheng, Yushan and Liu, Juncheng, year=2025, month=Sep., pages=595–608